2003
DOI: 10.1002/ptr.1227
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory and immunomodulatory activities of polysaccharide from Chlorella stigmatophora and Phaeodactylum tricornutum

Abstract: Crude polysaccharide extracts were obtained from aqueous extracts of the microalgae Chlorella stigmatophora and Phaeodactylum tricornutum. The crude extracts were fractionated by ion-exchange chromatography on DEAE-cellulose columns. The molecular weights of the polysaccharides in each fraction were estimated by gel filtration on Sephacryl columns. The crude polysaccharide extracts of both microalgae showed anti-inflammatory activity in the carrageenan-induced paw edema test. In assays of effects on the delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(98 citation statements)
references
References 13 publications
5
83
0
7
Order By: Relevance
“…These results are evidenced that the increased cell viability of the samples against LPS treated toxicity followed by significant suppression of NO production as well. Recently reported many publications have indicated that containing of anti-inflammatory components in P. tricornutum and Chlorella stigmatophora organic solvent extracts (Guzmán et al 2003). Therefore, these results were suggested that the strong anti-inflammatory activities were observed in the extracts and the fractions derived from the cultured marine microalgae in vitro assay.…”
Section: Anti-inflammatory Effect Of the Extracts And Fractions From mentioning
confidence: 83%
“…These results are evidenced that the increased cell viability of the samples against LPS treated toxicity followed by significant suppression of NO production as well. Recently reported many publications have indicated that containing of anti-inflammatory components in P. tricornutum and Chlorella stigmatophora organic solvent extracts (Guzmán et al 2003). Therefore, these results were suggested that the strong anti-inflammatory activities were observed in the extracts and the fractions derived from the cultured marine microalgae in vitro assay.…”
Section: Anti-inflammatory Effect Of the Extracts And Fractions From mentioning
confidence: 83%
“…[32][33][34][35] Few in vitro and in vivo studies on Chlorella extracts have shown anti-inflammatory, immunomodulatory, analgesic, and free radical scavenging activities. 36,37 Authors have reported that Chlorella short-term supplementation in uninfected normal people enhanced Natural Killer cell activity and early inflammatory response (serum concentration of interferon-c and interleukin-1b increased). 38 It is difficult to determine which compounds could be responsible for such immunomodulatory or analgesic effects as the microalgae Chlorella is a mix of many components as various as proteins, lipids, carbohydrates, pigments, and also not so well-characterized compounds yet such as growth factors, the whole probably having a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The extracts of PT show anti-inflammatory effects in the paw edema test and immunomodulatory effects in the delayed hypersensitivity test (Guzman et al, 2001). A pharmacological study of hydrosoluble and liposoluble extracts of the marine microalgae Chlorella stigmatophora and PT indicated that hydrosoluble components of both species show significant antiinflammatory, analgesic and free radical scavenging activity (Guzman et al, 2003). These activities were not detected in the liposoluble fractions (Guzman et al, 2001;.…”
Section: Discussionmentioning
confidence: 99%